The (anti)colonial Awit of Juan Tamad didacticism and subversion in a colonial metrical romance - Castillo, Laurence Marvin S. (Philippine studies : historical and ethnographic viewpoints, 2017)
"In the early decades of the twentieth century a metrical romance on the life of Juan Tamad, recounting the Westernized narrative of the adventures of the Tagalog numskull hero, Juan Tamad, was printed in Manila. This article links the text's literary hsitory to the discursive regimes of the Spanish and American colonial orders, and treats it as a heteroglossic text that carries the impulses of both clerical and secular didacticism and of radical anticolonial politics. Juan Tamad has since been the embodiment of the Filipino critical imagination in cultural permutations accross Philippine history, such as the cinema of Manuel Conde (1947-1963).